Chinese Whispers? The Congruence Between Maltese FE Organizations’ Missions and Government Policy For the Sector - Zarb, Nicholas (APMBA (Asia Pacific Management and Business Application), 2013)
This paper delineates the assessed alignment between the Maltese government’s policy for the further education sector (FE) and FE organizations’ missions. Since alignment is multifaceted, a complementarity blended approach was used to help uncover its complexities. Data were collected from seven FE vocational and academic organizations via questionnaires to academic staff; interviews with principals and other internal and external stakeholders; content analysis of mission statements. Data showed that there is only moderate alignment between organizational mission and government policy with large vocational organizations displaying more alignment with such policies.The use of a complementarity blended method may be useful to explain educational alignment in other small states. Short bureaucratic distances are not a guarantee of alignment.